Disintegration of sorghum pith caused by Macrophomina phaseolina in relation to foliage senescence - M.Y. SAMDUR, M.S. RAUT and APPAJI CHARI, ASHOK V. GADEWAR*, PRABHAKAR (Indian Phytopathology, 2013)
Investigations carried over several years under field conditions revealed that pith disintegration caused by Macrophomina phaseolina in sorghum plants is affected by leaf senescence. Leaf senescence recorded at 98 and 106th day of 163 sorghum test lines revealed fairly good correlation (r = 0.48 and 0.47) with pith rot and the correlation was significant which indicated pith disintegration is affected by leaf senescence. The mean rate (b) of senescence varied from trial to trial and ranged from 0.5 to 1.4, and individual test line senesced at a rate between 0.2 to 2.0 in six trials (2008-11). The rate of senescence also have positive relation with pith rot in test lines and the degree of relationship (r = 0.11 to 0.69) was more in popular cultivars than in test lines. The days to 50 per cent flowering had inverse (r = -0.31) significant relation with pith rot as well as with Charcoal rot (CR) incidence (r = -0.26) but charcoal rot incidence has been found to have significant correlation (r = 0.17) with pith rot. External cortical lesion produced on rind of sorghum plants by Macrophomina on inoculated plant has strong significant correlation (r = 0.95) with internal pith rot.